Reformas Neoliberais no Brasil: projeto político-econômico e impactos do Governo Temer (2016-2018) - Silva, Marcus Vinicius Rigonato da [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Em 2015, um documento assinado pela Partido do Movimento Democrático Brasileiro (PMDB, atual MDB) é lançado, ainda sob o governo da Presidente Dilma, com o nome “Uma Ponte para o Futuro”. No ano seguinte, devido ao impeachment, Dilma é tirada da presidência e, o Vice-Presidente, Michel Temer, assume o poder executivo. O Presidente Michel Temer assumiria então a tarefa de promover as reformas neoliberais presentes em “Uma Ponte para o Futuro”, aprofundando a política econômica do país que, desde Dilma, apresentava tendências neoliberais. O presente trabalho investiga as reformas do Governo Temer – teto de gastos e reforma trabalhista - em seus aspectos teóricos e práticos, neste último caso, de modo limitado, dado o curto distanciamento histórico e encerramento de algumas políticas. Ainda assim, a análise do período indica um aprofundamento do projeto neoliberal sem os resultados macroeconômicos esperados pelos defensores das políticas implementadas.

In 2015, a document signed by the Brazilian Democratic Movement Party (PMDB, now MDB) was released under President Dilma’s government, titled “A Bridge to the Future.” The following year, due to the impeachment, Dilma was removed from the presidency, and Vice President Michel Temer took over the executive power. President Michel Temer then undertook the task of promoting the neoliberal reforms outlined in “A Bridge to the Future,” deepening the country’s economic policy, which had already shown neoliberal tendencies during Dilma’s term. This paper examines Temer’s reforms— the Spending Cap and the Labor Reform — in both their theoretical and practical aspects, although the latter is limited due to the short historical distance and the conclusion of some policies. Nevertheless, an analysis of this period indicates a deepening of the neoliberal project without achieving the macroeconomic results expected by the proponents of the implemented policies.
Neoliberal reforms in Brazil: political-economic project and impacts of the Temer Government (2016-2018)
Keywords: Economia brasileira; Neoliberalismo; Brazilian economy; Neoliberalism